ETHNIC-SPECIFIC EFFECT OF APOE ALLELES ON EXTREME LONGEVITY. (11th November 2018) - Gurinovich, A; Bae, H; Andersen, S; Puca, A; Atzmon, G; Barzilai, N; Perls, T; Sebastiani, P
Abstract: Apolipoprotein E (APOE) is a well-studied gene with multiple effects on aging and longevity. The gene has 3 alleles: e2, e3 and e4 whose frequencies vary by ethnicity, and e4 is a known risk factor for Alzheimer's, while e2 is associated with healthy aging and longevity. We analyzed ethnic specific effects of APOE alleles on extreme human longevity using genetic data of about 9, 000 individuals from four studies of extreme longevity: the New England Centenarian Study, the Southern Italian Centenarian Study, the Longevity Gene Project, and the Long Life Family Study. The aggregated data comprised several European ethnicities and included 2144 cases of extreme longevity defined as individuals who lived past the 1 percentile survival age from the 1900 birth year cohort (i.e. age > 96 for males, and >100 years for females). For the analysis we used our new method PopCluster that combines logistic regression modeling, principal component analysis of genome-wide genetic data, hierarchical clustering, and a novel recursive bottom-up tree parsing procedure to automatically discover subsets of individuals in which the effects of a variant are statistically different. This analysis identified ethnically different clusters in which the effect of APOE e2 and e4 alleles on extreme longevity changed substantially. For example, PopCluster discovered a group of Southern Italians with weaker protective effect of APOE e2 and weaker damaging effect of APOE e4 on extreme longevity compared to other European ethnicities. These results suggest possible interaction of this gene with nutrition habits or other environmental factors.